Experimental study on the progressive collapse behaviour of RC flat plate substructures subjected to corner column removal scenarios. (1st February 2019) - Ma, Fuhao; Gilbert, Benoit P.; Guan, Hong; Xue, Huizhong; Lu, Xinzheng; Li, Yi
Highlights: The load resisting mechanisms and failure modes noticeably varied between different corner reinforcement configurations. The applied load was mainly transferred to edge columns adjacent to the removed corner column. The risk of progressive collapse can be reduced with the existence of overhangs surrounding a removed corner column. Yield line theory can be used to estimate the slab flexural capacities under corner column removal scenarios in this study. Abstract: Reinforced concrete (RC) flat plate structures are broadly used in car parks, residential and office buildings due to their economic and architectural advantages. However, this structural system is inherently prone to punching shear failure, which may propagate horizontally and vertically, ultimately leading to the progressive collapse of the entire structure or of a large portion of it. This paper presents the experimental results from two quasi-static large-displacement tests performed on a 1/3 scale, 2 × 2-bay, RC flat plate substructure subjected to corner column removal scenarios. The specimen was tested twice with different corner reinforcement configurations: (i) firstly, one corner column, with torsional strips, was removed and the Uniformly Distributed Load (UDL) on the bay adjacent to the removed column was increased to failure (Test T1), and (ii) secondly, as the damage was concentrated in the vicinity of removed corner column in (i), the corner column diagonally opposite to the first removed one, without torsional strips, was removed. The UDL on the bay adjacent to the second removed column was also increased to failure (Test T2). Different failure and post-failure behaviours, failure modes, and collapse resisting mechanisms between the two tests were witnessed, presented and analysed. Results show that 80% to 110% of the applied load is transferred to the two edge columns adjacent to the removed corner column throughout the entire two tests. The ultimate load carrying capacity for T1 is found to be 1.7 times smaller than the one for T2.